Students' perception on the using of Google Classroom for writing at vocational high school - Nanda Oetari Triana P; Tenny Murtiningsih; Hafizhatu Nadia (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2021)
The study is aimed at finding the students’ perception on the using of Google Classroom for writing skill at vocational high school. This research generally answered the question: What are student’s perception on the using of Google Classroom for writing skill? The data was collected through interviews. There were 5 students of tenth grade as the participant. This research explored the students’ perception which came from the students’ experiences during COVID-19 pandemic. It is descriptive research by using qualitative technique. The result showed varied answers yet so much positive after all. Keywords: Perception; Google Classroom; Writing skill